Intragenerational labor mobility in the Indian labor market - Bhaskar Jyoti Neog; Bimal Kishore Sahoo (IZA Journal of Development and Migration, 2020)
The present study contributes to the limited literature on labor mobility in India using the India Human Development Survey panel data for the years 2004-2005 and 2011-2012. We use three different tools, viz., transition matrices, multinomial logistic regression, and wage regressions for this study. The results show significant mobility across sectors in the economy. Mobility patterns among workers are found to differ significantly along the lines of gender, caste, education, wealth, and family background, among others. There is a distress-driven movement of workers. Significant earnings differentials exist across paid work statuses. The paper concludes with some policy suggestions.
Keywords: C23; C25; J31; J46; J62; 330; mobility; self-employment; gender; distress-driven employment; transition matrices